2018
DOI: 10.1371/journal.pone.0206597
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A protein distribution in mature inflamed and ischemic brain tissue

Abstract: BackgroundThe liver-derived plasma protein fetuin-A is strongly expressed during fetal life, hence its name. Fetuin-A protein is normally present in most fetal organs and tissues, including brain tissue. Fetuin-A was neuroprotective in animal models of cerebral ischemia and lethal chronic inflammation, suggesting a role beyond the neonatal period. Little is known, however, on the presence of fetuin-A in mature human brain tissue under different physiological and pathological conditions.MethodsWe studied by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In this regard, it has been suggested that fetuin-A plays a role in tissue remodeling during embryogenesis, its expression peaking during the transition from organogenesis and histogenesis, when cells acquire their final phenotype, but is lost thereafter 56 , 57 . Yet, recent evidence shows that fetuin-A expression is reactivated upon ischemic brain damage, aiding tissue repair 58 . In the developing kidney, prenatal hypoxia induces apoptosis 59 , 60 and was reported to cause renal vascular dysfunction 61 , 62 , giving rise to excess amounts of cellular debris that could serve as mineralization foci.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been suggested that fetuin-A plays a role in tissue remodeling during embryogenesis, its expression peaking during the transition from organogenesis and histogenesis, when cells acquire their final phenotype, but is lost thereafter 56 , 57 . Yet, recent evidence shows that fetuin-A expression is reactivated upon ischemic brain damage, aiding tissue repair 58 . In the developing kidney, prenatal hypoxia induces apoptosis 59 , 60 and was reported to cause renal vascular dysfunction 61 , 62 , giving rise to excess amounts of cellular debris that could serve as mineralization foci.…”
Section: Discussionmentioning
confidence: 99%
“…AHSG is secreted into the blood mainly by the liver and is also expressed in the cerebral cortex, thalamus, and hippocampus [ 45 , 46 ]. Based on previous studies, AHSG functions in the induction of inflammation and energy balance [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, Wang et al showed that fetuin-A supplementation reduced ischemic damage after permanent middle cerebral artery occlusion in rats [ 127 ]. Heinen et al also reported a reactivation of fetuin-A upon ischemic brain damage in humans, aiding tissue repair [ 39 ]. In addition to its function as vascular calcification inhibitor, the above findings and our results suggest a more general role for fetuin-A as an indirect regulator of calcification, fibrosis, inflammation, and macrophage polarization within tissues.…”
Section: A Protective Role Of Fetuin-a Beyond Vascular Calcificationmentioning
confidence: 99%